PERIODONTAL CHART DAN PERIODONTAL RISK ASSESSMENT SEBAGAI BAHAN EVALUASI DAN EDUKASI PASIEN DENGAN PENYAKIT PERIODONTAL - I Komang Evan Wijaksana (Jurnal Kesehatan Gigi, 2019)
The development of science and technology in the field of periodontology in digital era has experienced quite rapid development. However, this development is not comparable with community's periodontal tissue health that is fairly high. Data from RISKESDAS 2018 shows the percentage of periodontitis cases in Indonesia is 74.1%. Periodontal disease is an oral disease that ranks first in the 2001 world record book record as the most common disease in humans. The high periodontal prevalence data can be due to lack of patient’s knowledge of periodontal health or dental health practitioners who do not emphasize the importance of the health of periodontal tissue. The risk assessment of periodontal disease is still rarely done by dental health practitioners when compared with the assessment of the risk of dental caries. This article aims to introduce periodontal disease risk assessment methods and tools for dental health practitioners. Search for information on periodontal disease risk assessment methods and tools through PubMed with the keywords "periodontal charting" and "periodontal risk assessment". The periodontal disease risk assessment tool is chosen based on open access and free of charge. Periodontal charts and Periodontal Risk Assessment (PRA) are simple applications that can be used by all dental and oral health practitioners in explaining, evaluating and motivating patients with periodontal disorders. Periodontal chart and PRA can be used as material for evaluation and education of patient's periodontal tissue for dental health practitioners.